Exploration of weak interaction directed self-assemblies on reacting mononuclear copper(II)/nickel(II)⋯water host⋯guest systems of a double-compartment ligand with mono/di/tricarboxylic acids. (5th September 2015) - Ghosh, Sagar; Mandal, Leena; Mohanta, Sasankasekhar
Graphical abstract: The mononuclear host–guest systems [M II L OEt–en ⊂(H2 O)] (M = Cu/Ni; H2 L OEt–en  =  N, N′ -ethylenebis(3-ethoxysalicylaldimine)) are treated with o -chlorobenzoic acid, fumaric acid, succinic acid, terephthalic acid and 1, 3, 5-benzenetricarboxylic acid to produce eight weak interaction directed 1-D/2-D/3-D self-assemblies. The basic units of the self-assemblies are the 2:1 adducts [{M II L OEt–en ⊂(H2 O)}2 (dicarboxylic acid)], 1:1 adducts [{M II L OEt–en ⊂(H2 O)}(1, 3, 5-benzenetricarboxylic acid)] and 1:1 adduct [{Cu II L OEt–en ⊂(H3 O)}( o -chlorobenzoate)]. Abstract: The work in this report deals with the syntheses, characterization, molecular and supramolecular structures of eight compounds of the composition [{Cu II L OEt–en ⊂(H3 O)}( o -chlorobenzoate)] (1 ), [{Cu II L OEt–en ⊂(H2 O)}2 (fumaric acid)] (2 ), [{Ni II L OEt–en ⊂(H2 O)}2 (fumaric acid)] (3 ), [{Cu II L OEt–en ⊂(H2 O)}2 (succinic acid)] (4 ), [{Ni II L OEt–en ⊂(H2 O)}2 (succinic acid)] (5 ), [{Ni II L OEt–en ⊂(H2 O)}2 (terephthalic acid)] (6 ), [{Cu II L OEt–en ⊂(H2 O)}(1, 3, 5-benzenetricarboxylic acid)]·MeOH (7 ) and [{Ni II L OEt–en ⊂(H2 O)}(1, 3, 5-benzenetricarboxylic acid)]·MeOH (8 ), where H2 L OEt–en is N, N′ -ethylenebis(3-ethoxysalicylaldimine). These compounds are obtained on reacting the mononuclear host–guest compound [Cu II L OEt–en ⊂(H2 O)]/[Ni II L OEt–en ⊂(H2 O)], which contains a trapped water molecule, with the corresponding mono/di/tricarboxylic acid. One water molecule in2 –8 and one oxonium ion in1 is trapped in each O(phenoxo)2 O(ethoxy)2 compartment. Both the carboxylic acid groups of the dicarboxylic acids are involved in interacting with the trapped water molecule, forming the supramolecular dimers2 –6, while one of the three carboxylic acid groups of 1, 3, 5-benzenetricarboxylic acid is involved in O–H⋯O(trapped water) hydrogen bond, forming the 1:1 adducts7 and8 . Compound1 contains o -chlorobenzoate and the trapped species herein is the oxonium ion (H3 O + ). [{Cu II L OEt–en ⊂(H3 O)] + and o -chlorobenzoate fragments in1 are self-assembled because of an O–H(oxonium ion)⋯O(carboxylate) hydrogen bond. The above mentioned adducts are further self-assembled to generate 1-D/2-D/3-D supramolecular structures because of hydrogen bonds/π⋯π interactions/Ni II ⋯Ni II interactions/halogen bonds.